EFEKTIVITAS PENGGUNAAN LKM BERBASIS HOTS (HIGHER ORDER THINKING SKILLS) TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA - R, Nurmala; Mucti, Alfian (Journal of Honai Math, 2019)
The purpose of this study was to determine the effectiveness of the use of student activity sheet (SAS) based on Higher Level Thinking Skills (HOTS) on learning outcomes of mathematics student. This research is a quantitative, quasi-experimental method using the nonequivalent control group research design. Data collection uses documentation and tests to measure learning outcomes. The data obtained were analyzed statistically using descriptive analysis and inferential analysis. Descriptive analysis includes the mean value and standard deviation. The inferential analysis used in this study is one sample t-test and independent sample t-test. Based on the results of the analysis with a significance level of 5%, it can be concluded that the use of SAS based on Higher Level Thinking Skills (HOTS) is effective on student learning outcomes.